392 Effect of Obstructive Sleep Apnea Severity, Sleep Stage and Position on Patterns of Oximetric Desaturations and Resaturations. (3rd May 2021) - Thanaviratananich, Sikawat; Cheng, Hao; Pino, Maria; Sundar, Krishna
Abstract: Introduction: Obstructive sleep apnea (OSA) severity based upon the apnea-hypopnea index (AHI) ignores many characteristics such as the duration of apnea-hypopneas, the duration and degree of oxygen desaturations (SpO2) etc. While hypoxemic burden has received increased attention given its relationship with cardiovascular outcomes, the role of oximetric resaturation vs. desaturation times is not understood. Resaturation times tend to be constant in contrast to desaturation durations. This study was done to assess desaturation and resaturation indices in patients with different OSA severity in differing sleep stages and positions. Methods: Oximetric desaturation and resaturation slopes were calculated in patients with different OSA severities as rate of change in oxygen saturations (ΔSpO2/Δtime). Results: 33 patients with OSA were studied (11 in each OSA severity group). Mean desaturation duration was 20.12 ±1.10 seconds with shorter NREM desaturation times (mean 19.07 ±1.11 seconds) as compared to REM desaturation durations (mean 26.66 ±2.69 seconds) (p-value 0.009). Non-supine and supine mean desaturation durations were similar (19.59 ±1.77 and 18.73 ±1.18 seconds respectively). Mean resaturation durations were shorter than desaturation durations at 12.46 ±0.84 seconds and was significantly lower in NREM sleep than in REM sleep (9.32 ±0.41 seconds vs 12.50 ±0.75 seconds p-value 0.002). Resaturation slopes (0.44 %/second (±0.028 %/second)) were steeper as compared to desaturation slopes (-0.26 %/second (±0.02 %/second)) without significant difference between NREM vs. REM desaturation or resaturation slopes. While desaturation slopes were not affected by sleep position, resaturation slopes were significantly steeper in supine compared to non-supine sleep (p-value 0.0046). Desaturation durations increased with OSA severity, but resaturation times decreased (resaturation slopes became steeper) with significant differences between patients with different OSA severity. Conclusion: This study demonstrated that oxygen resaturation slopes varied according to different OSA severity and sleep position. Given that faster resaturation rates may reflect the possibility of higher degrees of reoxygenation-related oxidative stress, this should be assessed as a novel index to predicate OSA outcomes. Support (if any):